2015
DOI: 10.3748/wjg.v21.i32.9666
|View full text |Cite
|
Sign up to set email alerts
|

Radioembolisation and portal vein embolization before resection of large hepatocellular carcinoma

Abstract: Resectability of hepatocellular carcinoma in patients with chronic liver disease is dramatically limited by the need to preserve sufficient remnant liver in order to avoid postoperative liver insufficiency. Preoperative treatments aimed at downsizing the tumor and promoting hypertrophy of the future remnant liver may improve resectability and reduce operative morbidity. Here we report the case of a patient with a large hepatocellular carcinoma arising from chronic liver disease. Preoperative treatment, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…Although the present review depicted a substantial lower KGR for RE with values ranging between 0.3% and 2.5%, certain patient selection without heavily pretreated patients might overcome these low values, and this needs to be addressed in prospective trials. In case of insufficient hypertrophy levels after RE, the option of PVE/portal vein ligation or even a combination of transarterial and transportal RE is feasible [25,39,40]. To date, the only comparative study between RE and PVE, a matched-pair analysis, demonstrated a significantly higher mean relative hypertrophy level of 62% following PVE compared to a mean relative hypertrophy level of 29% following RE [23].…”
Section: Discussionmentioning
confidence: 99%
“…Although the present review depicted a substantial lower KGR for RE with values ranging between 0.3% and 2.5%, certain patient selection without heavily pretreated patients might overcome these low values, and this needs to be addressed in prospective trials. In case of insufficient hypertrophy levels after RE, the option of PVE/portal vein ligation or even a combination of transarterial and transportal RE is feasible [25,39,40]. To date, the only comparative study between RE and PVE, a matched-pair analysis, demonstrated a significantly higher mean relative hypertrophy level of 62% following PVE compared to a mean relative hypertrophy level of 29% following RE [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, the increase in hepatic arterial perfusion following PVE may have a growth effect on both primary and secondary liver tumors. This has led some investigators to explore the use of trans-arterial chemo-embolization (TACE), 21,22 or radioembolization using Yttrium-90 microspheres, 23 prior to PVE. These combined approaches are reported to induce greater hypertrophy of the FLR and atrophy of the HCC than PVE alone.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the coinciding anti-tumoral effect of RE allows for more time for the FLR to hypertrophy. And if FLR hypertrophy is insufficient after RE, subsequent PVE/PVL can be considered [ 46 , 62 ]. Another option might be combining transarterial and transportal RE.…”
Section: Discussionmentioning
confidence: 99%